Adaptation To The Credit-Modular System Of Education As A Pedagogical Problem (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article describes the possibilities of a credit-modular learning system for a student in the system of higher education. The functions of the credit-model system of education are disclosed in detail.